Crystallographic Orientation Dependence on Electrical Properties of (Bi, Na)TiO3‐based Thin Films. Issue 11 (13th August 2013) - Ding, Rui; Wang, Danyang; Chu, Dewei; Li, Sean
Abstract : Orientation‐engineered (La, Ce) cosubstituted 0.94(Bi0.5 Na0.5 )TiO3 –0.06BaTiO3 thin films were epitaxially deposited on CaRuO3 buffered (LaAlO3 )0.3 (Sr2 AlTaO6 )0.35 single‐crystal substrates by pulsed laser deposition. The ferroelectric, piezoelectric, dielectric, and leakage current characteristics of the thin films were significantly affected by the crystallographic orientation. We found that the (001)‐oriented film exhibited the best ferroelectric properties with remnant polarization P r  = 29.5 μC/cm 2 and coercive field E c  = 7.4 kV/mm, whereas the (111)‐oriented film demonstrated the largest piezoelectric response and dielectric permittivity. The bipolar resistive switching behavior, which is predominantly attributed to a combined effect of ferroelectric switching and formation/rupture of conductive filaments, was observed. The conduction mechanisms were determined to be ohmic conduction and Poole–Frenkel emission at high‐ and low‐resistance states, respectively, in all the films.